Pengaruh Pendidikan, Jumlah Tanggungan, Dan Jam Kerja Terhadap Pengeluaran Rumah Tangga Miskin Di Kota Denpasar - Ni Made Ayu Martiana Dewi; Made Heny Urmila Dewi (Universitas Veteran Bangun Nusantara, 2022)
Poverty is a state of not being able to meet basic needs such as clothing, shelter, food, health and education. The relatively large number of poor people in Indonesia proves that the policies that have been implemented have not been able to eradicate poverty. Poverty alleviation needs to be considered from various aspects, one of which is the micro aspect seen from the individual or family point of view. Households that are closely related to poverty have characteristics including a large number of household members, few hours of work, low education, geographical differences between cities and villages, business fields and employment status, access to clean water, adequate housing, utilization electricity and so on.The objectives of this study are: 1) to analyze the effect of education, number of dependents, and working hours simultaneously on the expenditure of poor households in Denpasar City, and 2) analyze effect of.education, number of dependents, and working hours partially on household expenditure poor households in Denpasar City. This research was conducted in Denpasar City with a total of 333 observations obtained based on the number of households whose expenditures were below the poverty line. The data analysis technique used is multiple linear regression.This study found the effect of education, number of dependents and working hours that affect simultaneously expenditure of poor households in Denpasar City. Partially, the education, number of dependent and working hour have a significant positive effect on the expenditure of poor households in Denpasar City.